The Violence of the Letter Toward a Theory of Writing - McMahon, Melanie (University of Michigan Press, 2023)
The emergence of the alphabet in ancient Greece, usually heralded as the first step in the inexorable march toward reason and progress, in fact signaled the introduction of a chance technology that hijacked the future, with devastating consequences for humanity. By investigating an array of cultural artifacts, ranging from Kubrick's 2001: A Space Odyssey to the Oracle at Delphi to Luther's challenge to the Church, this book demonstrates how the apparently benign emergence of writing made possible far-ranging systems of organized domination and unprecedented levels of violence. The Violence of the Letter considers how a twenty-six-letter code changed the face of the world, and not always for the better.